PENGGUNAAN STRATEGI PENGELOLAAN PERILAKU GURU PAI SEBAGAI PEMIMPIN, SURI TELADAN DAN TOKOH AGAMA SECARA EFEKTIF DALAM PEMBELAJARAN ABAD 21 - Sri Wahyuni; Irawan Irawan; Erni Haryanti (Universitas Muhammadiyah Ponorogo, 2026)
Many teachers are still unable to manage student behavior effectively in accordance with Islamic values and 21st-century character. This is certainly a problem that needs to be addressed considering the rapid development of education in the 21st century. It certainly requires a deeper understanding of 21st-century education in solving this problem. Therefore, the aim of this study is to analyze and identify how the use of behavior management strategies by Islamic education teachers as leaders, role models, and religious figures can be implemented effectively in 21st-century learning. This study uses a descriptive qualitative method. The descriptive qualitative method is a method that portrays, describes, and presents the object being studied based on the situation and conditions when the research is conducted. The recommended effective strategy is an integrative model that combines spiritual leadership, character strengthening, and 21st-century skills. In this model, teachers play not only the role of instructors but also as moral leaders who set examples and guide the formation of Islamic character in a tangible way. The success of this strategy depends greatly on the collaboration between teachers, schools, and the community, creating an educational environment that is comprehensive and supports the optimal development of students' character, morals, and competencies across various learning settings.